Engineering an empire. Volume 1 [videorecording (DVD)] - Weller, Peter, 1947- (History Channel : Distributed by New Video, 2007)
An architectural investigation beginning with Greece, the empire that gave rise to Western civilization and produced some of antiquity's greatest treasures. Next discover how Alexander saved the Greek Empire from its period of civil unrest, then voyage to Central America to unlock the mysterious and magical world of the ancient Aztecs.